Unveiling the Interplay of Sharia Investment Product Knowledge, Religiosity, and Financial Literacy as a Moderator of University Student’s Investment Decisions - Fachrozi; Kukuh Tondoyekti; Mariana; Herawati Khotmi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Sharia investment products is considered a key determinant in shaping University Student’s Investment Decisions among Muslim investors. A comprehensive understanding of the concepts, types, and characteristics of Sharia-compliant investments can significantly influence an individual's propensity to invest in accordance with Islamic principles. The purpose of this study aims to investigating the impact of Sharia investment product knowledge and religiosity on university students' Investment Decisions, with financial literacy serving as a moderator. The present study will employ a quantitative approach using a survey method. The data collection process will involve administering the questionnaire to the purposively selected sample Students, either through an online survey or in-person distribution on campus. The hypothesis is tested using version 3.37 of the Smart PLS program. The results showed that the Product Knowledge and Religiosity variables did not affect Investment Decisions. Meanwhile, Financial Literacy affects Investment Decisions. Financial Literacy is a moderating variable that only moderates the effect of Religiosity on Investment Decisions. As for the impact of Product Knowledge on Investment Decisions, it cannot moderate the effect of Religiosity on Investment Decisions.